MODAL ADVERB TRANSPOSITION IN OLD ENGLISH - Mykhaylenko, V.V. (Studia Philologica, 2016)
he present paper is based on the proposed classif cation of modal verbs in Old English and examines their relationship in the sentence and discourse structure. The shifts of modal adverbs in the sentence caused their grammatical transposition into sentential ones and then into discourse modal particles, respectively. The traditional role of an adverb is that of modifying a verb or a verb phrase expanded into that of modifying a sentence and then it developed the function of the linking element of discourse. Some explanations of their lexical, semantic, and functional features are discussed in the paper.